Analisis Kasus Fraud Korupsi Bantuan Sosial COVID-19 - Shella Shella; Natalis Christian; Fransiska; Julianti Cesilia; Nindi Suci Rahmadani; Sherly (Universitas Sarjanawiyata Tamansiswa, 2022)
As a type of fraud, corruption is a widespread global problem that adversely affects political stability, economic performance, and community integration. Corruption during a pandemic is very fatal, especially that involves public society, for example, in the case of Juliari Batubara. This study aims to analyze and interpret the corruption case related to the social assistance fund in COVID-19. This study uses a qualitative analysis method with a study case approach. This study uses secondary data obtained through books, journal articles, and websites. Study case analysis consists of categories of frauds, profile of victims, profile of fraudsters, motivation of fraudsters, impact of fraud, and fraud detection strategies, tools, and methods. Corruption can be detected through the KPK's whistleblowing system, such as JAGA and KWS. The results of this study are to provide implications, both theoretical and managerial. The theoretical implications of this research are to increase understanding of types of fraud, victim profiles, perpetrator profiles and motivations, impacts, and fraud detection. The managerial implications of this research are to analyze and identify elements related to fraud that occurred in Indonesia, namely the COVID-19 social assistance corruption case, as a reference for attention and improvement.